Pleural empyema caused by Actinomyces turicensis - Apostolos C. Agrafiotis; Ines Lardinois (New Microbes and New Infections, 2021)
Actinomyces turicensis was first identified in 1995. To the best of our knowledge, pleural empyema caused by A. turicensis has never been reported. In the case reported herein, a patient with pleural empyema was treated surgically, and in the bacterial samples, A. turicensis was isolated.